The Effect of Hepatocyte Growth Factor on Intestinal Adaption in an Experimental Model of Short Bowel Syndrome. (July 2018) - Bagias, George; Misiakos, Evangelos P; Charalampopoulos, Anastasios; Zavras, Nick; Sakellariou, Stratigoula; Sukhotnik, Igor; Giamarelos, Evangelos; Machairas, Anastasios
Abstract : Introduction: Short bowel syndrome (SBS) is a relatively uncommon syndrome which is defined as the functional loss of the 75% of normal short bowel length at least. To date, the standard therapy is the administration of total parenteral nutrition (TPN). However, long-term complications in patients with protracted PN are occurred. Intestinal transplantation is a potentially life-saving treatment for patients with severe SBS; its increased morbidity and mortality rates imply a careful preoperative consideration though. Moreover, the lack of compatible donor organs may delay significantly the transplantation. As a result, alternative therapies, like the administration of growth factors, in order to enhance intestinal adaptation acting as a bridge to transplantation have been emerged. The purpose of the present study is to evaluate the effect of hepatocyte growth factor (HGF) on structural intestinal adaptation, cell proliferation and apoptosis in a rat model of short bowel syndrome (SBS). Materials and Methods: Thirty Sprague-Dawley female rats were divided into three groups, sham rats underwent bowel transection (group A); SBS rats underwent a 75% bowel resection (group B); and SBS/HGF rats underwent bowel resection and were treated with HGF (75 μg/kg/d) (group C) starting at fourth postoperative day. All rats were sacrificed at 15th postoperative day. Parameters of intestinal adaptation (body weight, villus height and crypt depth in jejunum and ileum), enterocyte proliferation and enterocyte apoptosis were determined. A microarray analysis of RNA extracted from ileal samples was also carried out. Statistical analysis was performed using ANOVA test, with P<0.05 considered statistically significant. Results: Treatment with HGF (group C rats) resulted in significant increase in body weight compared to SBS rats (group B). The histopathologic analysis showed that jejunal and ileal villus height and crypt depth were significantly increased in HGF/SBS rats compared to SBS rats (36%, P<0.05 and 27%, P<0.05 respectively), showing that treatment with HGF enhanced the intestinal adaptation making intestinal absorption more efficient. Enterocyte proliferation was also significantly increased in HGF rats (21% P<0.05) compared to SBS rats; however we did not found any significant differences in enterocyte apoptosis rate between HGF/SBS and SBS rats. These findings indicate the augmentation of intestinal hyperplasia through HGF therapy. Microarray analysis of 22 genes showed that 12 genes were significantly up-regulated, and four genes were down-regulated in HGF/SBS rats compared to SBS rats; of note, some of these genes are involved in enterocyte proliferation/apoptosis pathway, indicating also that HGF therapy induces cell proliferation. Conclusion: HGF emerges as a growth factor that enhances intestinal adaptation in patients with short bowel syndrome. A future use of HGF may facilitate the prolonged TPN therapy while patients wait for intestinal transplantation.